Green communications for energy-efficient wireless systems and networks - Suraweera, Himal A.; Yang, Jing, 1981 May 30-; Zappone, Alessio; Thompson, John, 1970- (The Institution of Engineering and Technology, 2020)
The ICT industry is a major consumer of global energy. The energy crisis, global warming problems, dramatic growth in data traffic and the increased complexity of emerging networks are pushing academic and industry research towards the development of energy-saving and energy-efficient architectures, technologies, and networks to reduce the carbon footprint while ensuring efficient and reliable communication networks, and environmental sustainability. Attractive solutions for the design and implementation of energy efficient wireless networks and 5G technologies include massive MIMO, non-orthogonal multiple access, and energy harvesting communications. Tools from areas such as machine and deep learning are being investigated to establish optimal approaches and understand fundamental limits. Moreover, new promising heterogeneous and decentralized network architectures and the Internet-of-Things (IoT) will have an impact on the successful implementation of future and next generation green wireless communications. The aim of this edited book is to present state-of-the art research from theory to practice, and all aspects of green communication methods and technologies for the design of next generation green wireless communication systems and networks.
Keywords: Telecommunication -- Environmental aspects.; Sustainable engineering.; elektronické knihy; electronic books